Incidence of cancer among workers producing calcium carbide. Issue 4 (April 1986) - Kjuus, H; Andersen, A; Langård, S
Abstract : The overall mortality and the incidence of cancer have been studied among male employees at a plant producing calcium carbide. The cohort was defined as all men employed at the plant for at least 18 months in the period 1953 to 1970 and was classified according to 10 occupational categories. The 790 men have been observed from 1953 to 1983 and the incidence of cancer in the cohort has been compared with national incidence rates. A significant excess of colonic cancer (standardised incidence ratio, SIR = 2.09) and of prostatic cancer (SIR = 1.78) was found, and also a slight excess of lung cancer among furnace and maintenance workers (SIR = 1.56). The possible exposure of the workers to polycyclic aromatic hydrocarbons, asbestos, and cadmium is discussed.